Creative industries and the education. The school within culture transformations - Rey, Germán (Instituto para la Investigación Educativa y el Desarrollo Pedagógico, IDEP, 2018)
This article seeks to account the relationship between creative industries and the education, considering the key role of the school in cultural transformations  of the contemporary world. A tour for the evolution of the creative industries is made to, then, review their link with the school, always from the perspective of recognizing the meeting points that allow the construction of a society able to face the current challenges of the digital age.